The Process of Nonverbal Communication by Volunteers in Assisting Persons with Disabilities at Sahabat Difabel Lampung - Fieska Rusmeri; M. Denu Poyo; Wawan Hernawan (Indonesian Journal Publisher, 2026)
Volunteers who assist persons with disabilities must adapt their communication because spoken messages are not always sufficient. This study examines the process of nonverbal communication used by volunteers at Sahabat Difabel Lampung. The study employed a qualitative case-study approach within a constructivist paradigm. Data were collected through participant observation on two occasions, semi-structured interviews with nine informants, and document review. The informants consisted of one key informant, seven volunteer informants, and one supporting informant. Data were analyzed through reduction, display, and conclusion drawing, while source and technique triangulation were used to assess credibility. The findings show that volunteers begin by gaining attention and creating comfort through friendly facial expressions, eye contact, a calm approach, and appropriate physical distance. They then deliver messages through gestures, supportive touch, vocal cues, body position, sign language, writing, and digital media. Volunteers observe participants' responses and adapt the message to the individual and the situation. Instructions may be shortened, demonstrated, repeated, or transferred to a visual channel. When meaning remains unclear, volunteers check it again or seek assistance from another volunteer. These actions are interconnected rather than fixed in a linear sequence. Nonverbal communication therefore supports message delivery, mutual understanding, and the relationship between volunteers and persons with disabilities.